2021
DOI: 10.3390/molecules26185672
|View full text |Cite
|
Sign up to set email alerts
|

π–π Noncovalent Interaction Involving 1,2,4- and 1,3,4-Oxadiazole Systems: The Combined Experimental, Theoretical, and Database Study

Abstract: A series of N-pyridyl ureas bearing 1,2,4- (1a, 2a, and 3a) and 1,3,4-oxadiazole moiety (1b, 2b, 3b) was prepared and characterized by HRMS, 1H and 13C NMR spectroscopy, as well as X-ray diffraction. The inspection of the crystal structures of (1–3)a,b and the Hirshfeld surface analysis made possible the recognition of the (oxadiazole)···(pyridine) and (oxadiazole)···(oxadiazole) interactions. The presence of these interactions was confirmed theoretically by DFT calculations, including NCI analysis for experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 93 publications
1
18
0
Order By: Relevance
“…It should be mentioned that stacking interactions between heterocycles and the aromatic amino acid side chains Phe, Tyr, and Trp are a very attractive topic [ 56 ] in the frame of medicinal chemistry owing to the fact that heterocyclic scaffolds prevail between drugs in the market [ 57 , 58 , 59 , 60 ]. Boyarskiy et al [ 61 ] gave a detailed analysis of the π–π noncovalent interaction involving an oxadiazole system.…”
Section: Resultsmentioning
confidence: 99%
“…It should be mentioned that stacking interactions between heterocycles and the aromatic amino acid side chains Phe, Tyr, and Trp are a very attractive topic [ 56 ] in the frame of medicinal chemistry owing to the fact that heterocyclic scaffolds prevail between drugs in the market [ 57 , 58 , 59 , 60 ]. Boyarskiy et al [ 61 ] gave a detailed analysis of the π–π noncovalent interaction involving an oxadiazole system.…”
Section: Resultsmentioning
confidence: 99%
“…Now a convenient method for the synthesis of N,Ndialkyl-N'-pyridin-2-yl-substituted ureas as a result of one-step activation of the CÀ H bond in pyridine-Noxides has been developed in our research group. [70][71][72][73] In further study, we demonstrated that these pyridylureas can be converted to N-pyridylcarbamates via heating with an excess of corresponding alcohols [74] (Scheme 1). According to our study, this process occurred via isocyanate intermediate formation and it motivated us to extend this reaction to N-nucleophiles.…”
Section: Introductionmentioning
confidence: 96%
“…Now a convenient method for the synthesis of N , N ‐dialkyl‐ N‘ ‐pyridin‐2‐yl‐substituted ureas as a result of one‐step activation of the C−H bond in pyridine‐ N ‐oxides has been developed in our research group [70–73] . In further study, we demonstrated that these pyridylureas can be converted to N ‐pyridylcarbamates via heating with an excess of corresponding alcohols [74] (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…The structure and reactivity (including coordination with Pt(II)) of these compounds were studied [ 36 , 37 , 38 ]. In the present study we employed N , N -dialkyl- N ′-(pyridin-2-yl)-ureas, thus obtained, to synthesize novel Cu(II) complexes in the context of the global drug discovery efforts for metal-based tumor-suppressing agents.…”
Section: Introductionmentioning
confidence: 99%